Serum soluble intercellular adhesion molecule 1 and interleukin 8 levels in familial Mediterranean fever - (:unkn) unknown (J RHEUMATOL PUBL CO, 1999)
Objective, Familial Mediterranean fever (FMF) is a disease of unknown etiology characterized by recurrent attacks of polyserositis (peritonitis, pleuritis, and arthritis) and fever. We measured levels of soluble intercellular adhesion molecule 1 (sICAM-1) and interleukin 8 (IL-8), which are important mediators in leukocyte-endothelial adhesion and leukocyte accumulation in tissues. Methods. sICAM-1 and IL-8 levels were studied in 30 patients with FMF during attacks and remission, along with 23 healthy and 26 disease controls. sICAM-1 and IL-8 levels were measured with commercial ELISA systems. Results. Median levels of sICAM-1 were significantly elevated in patients with FMF during attacks (FMF-a) and remission periods (FMF-r) compared to healthy controls (HC) (FMF-a: 600 ng/ml, FMF-r: 520 ng/ml, HC: 353 ng/ml; FMF-a vs HC: p < 0.0001, FMF-r vs HC: p = 0.002). IL-8 levels were also significantly elevated in FMF-a compared to HC (37 vs 25 pg/ml; p = 0.009), but not during remission (26 pg/ml; p = 0.7). A significant correlation was observed between sICAM-1 and IL-8 levels (r = 0.33, p = 0.01). sICAM-1 levels also correlated significantly with erythrocyte sedimentation rate, C-reactive protein, and fibrinogen levels of patients with FMF. Conclusion. Increased levels of sICAM-1 and IL-8 in FMF suggest that neutrophils are active with increased adhesion in FMF Since increased levels of sICAM-1 are also observed during remission, subclinical disease activity and inflammation seem to be present in some patients.
Keywords: familial Mediterranean fever; interleukin 8; soluble intercellular adhesion molecule 1; TUMOR-NECROSIS-FACTOR; RHEUMATOID-ARTHRITIS; BEHCETS-DISEASE; FLUID